Public Consultation Processes in Greenland Regarding the Mining Industry - Ackrén, Maria (Arctic Review on Law and Politics, 2016)
Since the Greenland Self-Government Act came into force in 2009, economic development and the right to utilize natural resources in Greenland lies in the hands of the Self-Government. Earlier efforts to establish this authority were made back in the 1970s, when discussions on Home Rule were first on the agenda. Mining industries are not a new activity in Greenland. During the Second World War, Greenlandic cryolite was used to produce aluminum for the North American aircraft industry. Other essential natural resources, such as gold and gemstones, have also received international interest over the years. Greenland’s new development aim is to build up a large-scale mining industry. This article elucidates the form of public consultation processes followed in Greenland in connection with two large-scale mining projects and the different views various actors have regarding these events. How did the deliberative democratic process unfold in Greenland regarding these projects? Was the process followed an effective way to manage these kinds of projects? The article shows that two projects that received a lot of media attention: the 2005 iron ore mine project in Isukasia, and the 2001 TANBREEZ-project to extract rare earth elements, used highly different approaches when it comes to deliberative democracy. In the former case, a limited degree of deliberative democracy was used, while in the latter case, the opposite applies.(Published: May 2016)Citation: M. Ackrén. “Public consultation processes in Greenland regarding the mining industry.” Arctic Review on Law and Politics, Vol. 7, No. 1, 2016, pp. 3–19. http://dx.doi.org/10.17585/arctic.v7.216